Fetal Valproate Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The high frequency of minor abnormalities and major malformations, the withdrawal manifestations, and hypoglycemia in infants born to mothers who received sodium valproate during pregnancy are reported from the Department of Paediatrics, Aalborg Hospital, Denmark.